Multi‐Interfaces Regulated Polyaniline/Nano‐Fe3O4/Graphene Ternary Hybrids for Ultra‐Broadband Electromagnetic Absorption. Issue 12 (23rd September 2022) - Song, Xiaolong; Chen, Xiangnan; Gou, Guangjun; Xu, Hairui; Zhang, Zhiyong; Cui, Liying; Peng, Tianxiang; Zhu, Shibu
Abstract: Graphene‐based electromagnetic absorbing materials have attracted growing attention, due to their great absorption efficiency and light weight. One common design principle is to load magnetic particles onto graphene. However, the agglomeration of magnetic nanoparticles on the graphene sheets limits further improvement in their electromagnetic absorption performances. In this work, polyaniline/nano‐Fe3 O4 /graphene ternary hybrids with regulated multi‐interfaces are designed by simply adjusting the adding order of graphene. The dispersion of nano‐Fe3 O4 on graphene and the interactions among the ternary interfaces are synchronously controlled, which are considered to be the key factors restricting the hybrids' performances. The polyaniline/nano‐Fe3 O4 /graphene ternary composites show ultra‐broadband electromagnetic absorption, with the optimal reflection loss peak reaching −57.2 dB at 11.4 GHz, and the effective bandwidth achieves 13.2 GHz, covering 4.8–18 GHz. It is found that the well dispersion of nano‐Fe3 O4 can enhance the overall ferromagnetism and magnetic losses, while the modulation of the multi‐interfaces can further ameliorate the interfacial and dipole polarization, synergistically making the ultra‐broadband electromagnetic absorption. This work provides areferencing path for the design of subsequent multi‐interfacing electromagnetic absorbing materials. Abstract : Polyaniline/nano‐Fe3 O4 /graphene ternary hybrids with regulated multi‐interfaces are designed by adjusting the adding order of graphene. The dispersion of nano‐Fe3 O4 on graphene and the ternary interfaces are synchronously controlled, which are considered to be the key factors restricting the hybrids' performances. The well dispersion of nano‐Fe3 O4 onsite graphene and the modulation of the multi‐interfaces synergistically make the ultra‐broadband electromagnetic absorption.